Preparation of Al2O3–B4C thin-wall tube pellet by powder injection molding - MA Liang; YANG Jing; WANG Ji-ping; XU Kui (Fenmo yejin jishu)
The annular Al2O3–B4C thin wall tube with the wall thickness of near 0.7 mm was successfully sintered by powder injection molding combined with the solvent degreasing and thermal degreasing, using the multi-component wax-based binder. The results show that, when the paraffin mass fraction is 45%, the feedstock has the lower viscosity and the better bending strength. When the solid phase volume fraction is 58%, the feedstock has the good performance in the premise of low viscosity. When the sintering temperature is in the range of 1550 ℃ to 1650 ℃, the relative density and the bending strength of the pellets increase with the increase of temperature. When the sintering temperature reaches 1650 ℃, the density and strength of the pellets begin to decrease slightly, the density increases with the increase of the B4C particle size, and the bending strength increases first and then decreases with the increase of particle size.